Antibiotic Bacillomycin D Affects Iron Acquisition and Biofilm Formation in Bacillus velezensis through a Btr-Mediated FeuABC-Dependent Pathway - Xu, Zhihui; Mandic-Mulec, Ines; Zhang, Huihui; Liu, Yan; Sun, Xinli; Feng, Haichao; Xun, Weibing; Zhang, Nan; Shen, Qirong; Zhang, Ruifu (Cell reports (Cambridge), 2019)
Bacillus spp. produce a wide range of secondary metabolites, including antibiotics, which have been well studied for their antibacterial properties but less so as signaling molecules. Previous results indicated that the lipopeptide bacillomycin D is a signal that promotes biofilm development of Bacillus velezensis SQR9. However, the mechanism behind this signaling is still unknown. Here, we show that bacillomycin D promotes biofilm development by promoting the acquisition of iron. Bacillomycin D promotes the transcription of the iron ABC transporter FeuABC by binding to its transcription factor, Btr. These actions increase intracellular iron concentration and activate the KinB-Spo0A-SinI-SinR-dependent synthesis of biofilm matrix components. We demonstrate that this strategy is beneficial for biofilm development and competition with the Pseudomonas fluorescens PF-5. Our results unravel an antibiotic-dependent signaling mechanism that links iron acquisition to biofilm development and ecological competition. [Display omitted] •Increasing intracellular iron concentrations serves as a cue for biofilm development•Bacillomycin D controls transcription of the specific iron transport gene feuABC•Bacillomycin D directly binds to the iron transport regulator Btr•Bacillomycin D modulates biofilm formation through the KinB-Spo0A-SinI-SinR pathway Natural lipopeptides are known antibiotics produced by Bacillus spp. Xu et al. demonstrate that the lipopeptide antibiotic bacillomycin D is involved in biofilm formation by promoting the acquisition of iron. Versatile functions of bacillomycin D in B. velezensis contribute to the microbe’s ability to compete in its ecosystem.